Diagnostic criteria of small sellar lesions with hyperprolactinemia: Prolactinoma or else - Cho, Anna; Vila, Greisa; Marik, Wolfgang; Klotz, Sigrid; Wolfsberger, Stefan; Micko, Alexander (Frontiers in Endocrinology, 2022)
Objective To evaluate the combined predictive value of MRI criteria with the prolactin-volume-ratio (PVR) to differentiate prolactinoma from non-prolactinoma, in small sellar lesions with hyperprolactinemia. Methods Retrospective analysis of 55 patients with sellar lesions of ≤15 mm diameter on MRI and hyperprolactinemia of ≤150 ng/mL, surgically treated between 2003 and 2020 at the Medical University of Vienna, with a conclusive histopathological report. Serum prolactin levels, extent of pituitary stalk deviation, size and volume of the lesion were assessed. The PVR was calculated by dividing the preoperative prolactin level by tumor volume. Results Our study population consisted of 39 patients (71%) with a prolactin-producing pituitary adenoma (group A), while 16 patients (29%) had another type of sellar lesion (group B). Patients in group A were significantly younger (p=0.012), had significantly higher prolactin levels at diagnosis (p<0.001) as well as smaller tumor volume (p=0.036) and lower degree of pituitary stalk deviation (p=0.009). The median PVR was significantly higher in group A (243 ng/mL per cm3) than in group B (83 ng/mL per cm3; p=0.002). Furthermore, the regression operating characteristics analysis revealed a PVR >100 ng/mL per cm3 to be predictive for distinguishing prolactin-producing lesions from other small sellar lesions. Conclusion In patients with small sellar lesions, Prolactin-Volume-Ratios >100 represents a possible predictive marker for the diagnosis of prolactin-producing pituitary adenomas.